Significantly improved interfacial and overall mechanical properties of aramid fiber/phenolic resin matrix composite reinforced with short CNT - Mengjie Wang; Jianfang Yong; Lijuan Cai; Zhaojing Li; Yunfu Ou; Lingzhuang Zhu; Xiaosu Yi; Dongsheng Mao (Journal of Materials Research and Technology, 2023)
Aramid fiber-phenolic matrix composite laminates reinforced with carbon nanotubes (CNT) were developed, and their interfacial and mechanical properties were systematically investigated. Results revealed that short length of the CNT (≤1 μm in average length) (Short CNT) was critical to the performance of the laminates. Long CNT (∼10 μm) cannot effectively improve the properties of the laminates. Excellent dispersion and functionalization of the CNT are also conduced to improve the properties. The laminates reinforced with 3.0 wt% of the short/carboxylic functionalized CNT (Short CNT-COOH) in the phenolic matrix showed improvements of 17.7%, 49.6% and 22.3% in tensile strength, modulus and flexural strength, respectively, as compared with the control sample without CNT. No obvious improvement of the properties was seen based on Long CNT reinforcement. The interfacial shear strength and the wettability between the single aramid fiber and the matrix were significantly improved with CNT reinforcement. A detailed analysis was performed and reported.